Sondeo de niveles de lectura en evaluación diagnóstica inicial. Importancia de su realización en la práctica docente preprofesional (Experiencias) - Grilli Silva, Javier (2022)
The pre-professional practice in the initial training of a teacher is a key moment to elaborate, apply and process an initial diagnostic test that probes reading comprehension skills. This paper presents an experience carried out in the training of Biology and Spanish teachers in Uruguay. The evaluation shows very low reading comprehension of the students on average, and low levels at which they enter the teaching career, for the different reading levels: literal, inferential, evaluative and creative. The results of the diagnosis contributed to strengthen in the practicing teachers the realization of a didactic planning that to the objectives of: scientific literacy, prioritizing the use of the text as a didactic resource for the teaching of science, valuing the sustained work of macro skills linguistics.